Upaya penanaman karakter rajin pada anak usia dini - Wibisono, Audi; Sugianto, Everson; Velicia Gela, Kathryn; Linawati, Nanik (Penamas: Journal of Community Service, 2024)
For four days, community service activities were given to early childhood children at Rainbow Kiddy Kindergarten, Surabaya. Eight children participated, and all of them were kindergarten B students. The aim of holding this activity was to provide understanding and instill habits for productive and diligent living. The learning method is done through puppet stages that present educational stories, block assembly games, drawing on scratch paper, puzzle games, and coloring fans and piggy banks. The results of this community service activity show that the socialization activity has made children understand the importance of being diligent. Puzzle games and assembling blocks train children's motoric, sensory, and mental cognitive abilities to make efforts. Drawing activities on scratch paper and coloring fans encourage children to be more expressive and creative. Coloring piggy banks encourages creativity and the intention to start saving.